Contributions of the old urban homegardens for food production and consumption in Rio Claro, Southeastern Brazil - Eichemberg, Mayra Teruya; Amorozo, Maria Christina De Mello [UNESP] (MCTI/Museu Paraense Emílio Goeldi, 2013)
Urban homegardens are green areas of households within the city limits and they have the potential to provide families with a cheap alternative for diet improvement, and to complement the income of the families who sell cultivated products. This research analyzes the contributions of old urban homegardens on food consumption and household economy. Data related to homegardens composition were collected by interviews and by collecting cultivated plants. Diets were assessed through a retrospective method (last 24 hours food recall) and administered every two months, during a year, to include seasonal variations. The diet of the sampled population was found to be dependent on certain foods, indicating a narrow food niche (Levins index = 25.9; Levins standardized index = 0.23). Variations in interviewees' diet are related to the consumption of fruits and vegetables, which are partly supplied by homegardens. Spices and teas consumed were obtained from homegardens, revealing its importance in food consumption and health. Among the 98 species found in homegardens, only 38% appeared in the interviewees' diet, indicating an under-exploitation of these homegardens. Our study found that the main role of homegardens is to supply variation in the diet, contributing to the consumption of different types of products.

Os quintais urbanos correspondem às áreas verdes domiciliares dentro dos limites urbanos e têm o potencial de fornecer às famílias uma alternativa barata para a melhoria da dieta e complementação da renda familiar, pela venda de itens produzidos nesse espaço. Este estudo analisa a contribuição dos quintais urbanos antigos na alimentação e na economia doméstica. Os dados sobre a composição dos quintais foram obtidos por meio de entrevistas e pela coleta de plantas presentes nos quintais. As dietas foram levantadas pelo método recordatório das últimas 24 horas, aplicado bimensalmente, durante um ano, para incluir variações sazonais. Verificou-se que a dieta da população amostrada é dependente de alguns alimentos, indicando um nicho alimentar estreito (índice de Levins = 25,9; Levins padronizado = 0,23). As variações nas dietas dos informantes estão relacionadas com o consumo de frutas e hortaliças, em parte fornecidas pelo quintal. Temperos e chás consumidos foram obtidos dos quintais, revelando sua importância para alimentação e saúde. Das 98 espécies alimentares encontradas nos quintais, apenas 38% apareceram na dieta dos entrevistados, indicando uma subexploração dos quintais. Em nosso estudo, a principal função relatada para os quintais foi proporcionar variações da dieta, contribuindo para o consumo de itens diversificados.
Contribuições dos quintais urbanos antigos na produção e no consumo de alimentos em Rio Claro, Sudeste do Brasil
Keywords: Dieta; Etnobotânica; Nicho alimentar; Agricultura urbana; Diet; Ethnobotany; Food niche; Urban agriculture